An Externally Validated Model to Predict Prolonged Induction of Labor with an Unfavorable Cervix - Kawakita, Tetsuya; Saeed, Haleema; Huang, Jim C. (American Journal of Perinatology, 2023)
Objective To develop and externally validate a prediction model to calculate the likelihood of prolonged induction of labor (induction start to delivery time > 36 hours).Study Design This was a retrospective cohort study of all nulliparous women with singleton pregnancies and vertex presentation at term who underwent induction of labor and had a vaginal delivery at a single academic center. Women with contraindications for vaginal delivery were excluded. Analyses were limited to women with unfavorable cervix (both simplified Bishop score [dilation, station, and effacement: range 0–9] <6 and cervical dilation <3 cm). Prolonged induction of labor was defined as the duration of induction (induction start time to delivery) longer than 36 hours. A backward stepwise logistic regression analysis was used to identify the factors associated with prolonged induction of labor by considering maternal characteristics and comorbidities as well as fetal conditions. The final model was validated using an external dataset of the Consortium on Safe Labor after applying the same inclusion and exclusion criteria. We developed a receiver observer characteristic curve with area under the curve (AUC) in validation cohorts.Results Of 2,118 women, 364 (17%) had prolonged induction of labor. Factors associated with prolonged induction of labor included body mass index at admission, hypertension, fetal conditions, and epidural. Factors including younger maternal age, prelabor rupture of membranes, and a more favorable simplified Bishop score were associated with a decreased likelihood of prolonged induction of labor. In the external validation cohort, 4,418 women were analyzed, of whom 188 (4%) had prolonged induction of labor. The AUC of the final model was 0.76 (95% confidence interval: 0.73–0.80) for the external validation cohort. The online calculator was created and is available at: https://medstarapps.org/obstetricriskcalculator.Conclusion Our externally validated model was efficient in predicting prolonged induction of labor with an unfavorable cervix.Key Points
Keywords: Consortium on Safe Labor; external validation; labor induction; term pregnancy; unfavorable cervix